Auxin, cytokinin and ethylene differentially regulate specific developmental states associated with shoot bud morphogenesis in leaf tissues of mangosteen (Garcinia mangostana L.) cultured in vitro - Lakshmanan, P. (2014)
Plant and Cell Physiology